MicroRNA-451a is a candidate biomarker and therapeutic target for major depressive disorder - Yan Chen; Yun Liu; Ming Xiao; Chun Wang; Panpan Hu; Qiuchen Cao; Hu Feng; Jingfan Xu; Weixi Feng; Huaiqing Sun; Huachen Ding; Junying Gao (General Psychiatry)
Background Increasing evidence supports the role of microRNAs (miRNAs) in major depressive disorder (MDD), but the pathophysiological mechanism remains elusive.Aims To explore the mechanism of microRNA-451a (miR-451a) in the pathology and behaviours of depression.Methods Abnormal miRNAs such as miR-451a reported previously in the serum of patients with MDD were screened and then confirmed in a mouse model of depression induced by chronic restraint stress (CRS). Eight-week-old male C57BL/6 mice had miR-451a overexpression in the medial prefrontal cortex (mPFC) via adeno-associated virus serotype 9 vectors encoding a pri-mmu-miR-451a-GFP fusion protein followed by behavioural and pathological analyses. Finally, molecular biological experiments were conducted to investigate the potential mechanism of miR-451a against depression.Results The serum levels of miRNA-451a were significantly lower in patients with MDD, with a negative correlation with the Hamilton Depression Scale scores. Additionally, a negative association between serum miR-451a and behavioural despair or anhedonia was observed in CRS mice. Notably, miR-451a expression was significantly downregulated in the mPFC of CRS-susceptible mice. Overexpressing miR-451a in the mPFC reversed the loss of dendritic spines and the depression-like phenotype of CRS mice. Mechanistically, miR-451a could inhibit CRS-induced corticotropin-releasing factor receptor 1 expression via targeting transcription factor 2, subsequently protecting dendritic spine plasticity.Conclusions Together, these results highlighted miR-451a as a candidate biomarker and therapeutic target for MDD.